Modern Characteristics of Water Bodies in Ukraine: Watercourses and Reservoirs - Хільчевський, Валентин Кирилович (Київський національний університет імені Тараса Шевченка, 2021)
According to the assessment made in the article, the current data on the number of water bodies on the territory of Ukraine are: 63119 rivers; about 20 thousand lakes; 1054 reservoirs; 50793 ponds. There are rivers in Ukraine: large (> 50 thousand km2) – 8 rivers: Dnieper, Dniester, Danube, Desna, Pripyat, Southern Bug, Seversky Donets, Tisa; medium (2.0-50 thousand km2) – 82 rivers; small (<2.0 thousand km2) – 63,029 rivers (99.87%). There are lakes in Ukraine: very large (> 100 km2) – 1 lake: Yalpug; large (10-100 km2) – 21 lakes; medium (1-10 km2) – about 70; small (0.5-1.0 km2) and very small (<0.5 km2) – all other lakes (99.54%). There are reservoirs in Ukraine: very large (10-50 km3) – 2 reservoirs: Kremenchug and Kakhovskoe – on the river.Dnipro (0.2%); large (1.0-10 km3) – 5 reservoirs; Kievskoe,Kanevskoe, Kamenskoe, Dneprovskoe (on the Dnieper river), Dnestrovsky – on the Dniester (0.5%); medium (0.1-1.0 km3) – 11 reservoirs (1.0%); small (0.01-0.1 km3) – 88 reservoirs (8.4%); small (<0.01 km3) – 948 reservoirs (89.9%). There are ponds in Ukraine: very large (> 500 thousand m3) and large (200-500 thousand m3) – 13%; medium (50-200 thousand m3) – 29%; small (10-50 thousand m3) and very small (<10 thousand m3) – 58%. Of great importance was the approval by the Verkhovna Rada of Ukraine in 2016 of the hydrographic zoning of the territory of Ukraine with the allocation of 9 regions of river basins: the Dnieper, Dniester, Danube, Southern Bug, Don, Vistula, Crimean rivers Black Sea rivers, Azov rivers. Almost all rivers of Ukraine belong to the basin of the Black and Azov seas. In addition to the area of the river basin Vistula (Western Bug and San rivers) which belongs to the Baltic Sea basin and occupies only 2.5% of the country’s territory. It is shown that since hydrographic studies in Ukraine were carried out more than 50 years ago, modern hydrographic surveys of the country’s territory with the creation of a modern water cadastre and the establishment of real morphometric parameters of water bodies (rivers, lakes, reservoirs, ponds) are necessary. The main organizations dealing with these issues are the State Agency for Water Resources of Ukraine and the Ukrainian Hydrometeorological Center of the State Service of Ukraine for Emergency Situations. It is also necessary to regulate a number of concepts that are used a priori, but do not have a definition, clear parameters (for example, a stream, a source, a digging pond, etc.). This is difficult to implement through the Water Code of Ukraine or state standards, but it can be easier to do through the officially approved methods in which these terms are used.

За виконаним у статті оцінюванням, сучасні дані по кількості водних об’єктів на території України становлять: 63119 річок; близько 20 тис. озер; 1054 водосховища; 50793 стави. Оскільки гідрографічні дослідження в Україні виконувалися понад 50 років тому, необхідними є сучасні гідрографічні обстеження території країни зі створенням сучасного водного кадастру і встановленням реальних морфометричних параметрів водних об’єктів (річок, озер, водосховищ, ставів). Основними організаціями, у сферу діяльності яких входять ці питання, є Державне агентство водних ресурсів України та Український гідрометеорологічний центр Державної служби України з надзвичайних ситуацій. Необхідно також унормувати низку понять, які застосовуються апріорі, але не мають визначення, чітких параметрів (наприклад, струмок, джерело, став-копанка та ін.). Це складніше здійснити через введення доповнень у Водний кодекс України або ДСТУ, але можна зробити шляхом розробки офіційно затверджених методик, в яких дані терміни застосовуються.
Сучасна характеристика поверхневих водних об’єктів України: водотоки та водойми
Keywords: водні об’єкти; водотоки; водойми; річки; озера; водосховища; стави; water bodies; watercourses; reservoirs; rivers; lakes; ponds